Gambaran Uveitis Anterior pada Dewasa di RSUD Waled Tahun 2023-2024 - Fadilla, Rahma Nur; Astuti, Widi; Wirandoko, Ignatius Hapsoro (Syntax Corporation, 2025)
Ocular inflammation is an immune response to infection, irritation, autoimmune disease, allergies, or trauma that can affect both extraocular and intraocular structures. Anterior uveitis is an inflammation of the anterior part of the uveal tract, which has the potential to cause a significant decrease in vision up to blindness if left untreated. Its causes vary, ranging from infectious, non-infectious, to idiopathic factors. To describe the distribution and frequency of adult patients with anterior uveitis at RSUD Waled, Cirebon Regency, in 2023–2024, based on age, sex, clinical symptoms, visual acuity, and intraocular pressure. This research is a descriptive observational study using secondary data obtained from medical records in RSUD Waled 2023-2024 that met the inclusion and exclusion criteria. The majority of anterior uveitis patients in this study were middle-aged adults aged >40–60 years (56,5%) and predominantly female (54,3%). The most common clinical symptom was visual impairment, reported in 45 (35,3%) patients. Visual acuity was mostly categorized as good (44,6%) in the right eye and (40,2%) in the left eye. Intraocular pressure was mostly within the normal range (53,3%). Anterior uveitis in this study was most commonly found in middle-aged adults, and females. The most frequent clinical symptom was visual impairment. Most patients had visual acuity in the good category, and intraocular pressure remained within the normal range.